2009
DOI: 10.1007/s00417-009-1095-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical findings of vitreoretinal interface in eyes with asteroid hyalosis

Abstract: These results indicate that complete PVD appears to be unlikely to occur in eyes with AH. In addition, spontaneous PVD in eyes with AH might lead to vitreoschisis or residual whole layer or posterior vitreous cortex, possibly due to anomalous vitreoretinal adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
2
16
0
2
Order By: Relevance
“…The nature of preoperative VHDs can be aggregation of collagen fibrils [21] or asteroid bodies presenting as hyper-reflective lesions in OCT. [22], [23] The vitreous body contains hyalocytes and fibroblasts, although the number is small. [24] Hyalocytes range from 10 to 15 µm in diameter, and fibroblasts are usually localized in the cortex near the ciliary processes, vitreous base, and adjacent to the optic disc.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of preoperative VHDs can be aggregation of collagen fibrils [21] or asteroid bodies presenting as hyper-reflective lesions in OCT. [22], [23] The vitreous body contains hyalocytes and fibroblasts, although the number is small. [24] Hyalocytes range from 10 to 15 µm in diameter, and fibroblasts are usually localized in the cortex near the ciliary processes, vitreous base, and adjacent to the optic disc.…”
Section: Discussionmentioning
confidence: 99%
“…Mochizuki et al found that even in AH cases where it initially appeared that a PVD was present, it was common for the vitreous cortex to be found in the posterior retina and for vitreoschisis to be present [3]. However, even in AH cases, there are cases such as our case in which a complete PVD had occurred and the ABs were concentrated in the anterior vitreous.…”
Section: Discussionmentioning
confidence: 70%
“…It is characterized by a mild liquefaction of the vitreous body and a reduced likelihood of a posterior vitreous detachment (PVD) [2, 3]. Ophthalmoscopic examinations of eyes with AH show many light-yellow plaques which give the appearance of stars or asteroid bodies (ABs) shining in the night sky.…”
Section: Introductionmentioning
confidence: 99%
“…These vitreous remnants are often prominent sheets that result from splitting of the posterior vitreous cortex, known as vitreoschisis, which has been identified in half of the eyes with macular hole or macular pucker. [23][24][25][26][27][28][29][30][31][32] Splitting of the retina can result in lamellar macular holes (see below). Vitreopapillary adhesion is found in nearly all full-thickness and lamellar macular holes and vitreomaculopathies with intraretinal cysts.…”
Section: Vitreoretinal Pathologiesmentioning
confidence: 99%